First eigenvalue of the Laplace operator and mean curvature - Etemad, A. (Український математичний журнал, 2008)
The main theorem of this paper states a relation between the first nonzero eigenvalue of Laplace operator and the squared norm of mean curvature in irreducible compact homogeneous manifolds under spatial conditions. This statement has some results that states in the remainder of paper.